70 Introduction of a multidisciplinary neuro-oncology long-term follow-up clinic at GOSH during the covid-19 pandemic: experience of the past 18 months. (15th December 2021) - Gan, Hoong-Wei; Dahl, Christine; Blount, Nicola; Bell, Daniel; Farrell, Nicola; Hatton, Philippa; King, Vicky; Malcolm, Charlotte; Simcox, Angela; Michalski, Antony
Abstract : Background: The number of children and young people (CYP) surviving brain tumours is increasing annually, with 5-year survival having nearly doubled over the past 40 years. However, more than two-thirds of these survivors have multiple long-term co-morbidities ('late effects') resulting from their tumour and/or treatment(s) necessitating lifelong follow-up from multiple professionals. Objective: We sought to establish a collaborative multidisciplinary 'one-stop shop' long-term follow-up clinic for CYP who were >5 years from the end of treatment of a brain tumour to reduce the need for multiple hospital appointments and to provide holistic assessment and supportive care. Results: The first clinic began in January 2020 as a collaborative effort between healthcare professionals in the neuro-oncology, endocrinology, psychology, neuropsychology, physiotherapy and occupational therapy departments. Clinics ran once to twice-monthly throughout the year, and apart from a 6-month period during the Covid-19 pandemic, all appointments were carried out face to face. Over 18 months, a total of 61 patients have been seen in 111 appointments. Apart from neuro-oncology, CYP also had endocrinology (97%), neuropsychology (65%), physiotherapy/occupational therapy (55%) and psychology (53%) needs. Other specialties not represented in the clinic who were still involved in the care of these CYP included ophthalmology (57%), audiology (30%), neurology (22%) and CAMHS (22%). Feedback from CYP and their families thus far has been overwhelmingly positive, with all leaving feeling very satisfied or satisfied. Major issues include continued funding, the lack of clinic room space, and the appropriateness of the whole team seeing some CYP at the same time. Conclusions: Few models of similar multidisciplinary neuro-oncology long-term follow-up clinics exist in the UK, and streamlined funding of such services is sorely needed, despite the recognition from both families and professionals about their utility.